Comparison of vaporization models for feed droplet in fluid catalytic cracking risers - Nguyen, Thanh Vinh; Mitra, S.; Pareek, Vishnu; Joshi, J.; Evans, G. (Institution of Chemical Engineers, 2015)
Vaporization of atomized feedstock is one of the critical processes in fluid catalytic cracking (FCC) risers; which is more often ignored in most of the FCC riser modelling studies. In this study, two different vaporization mechanisms of feedstock namely homogeneous mode and heterogeneous mode were studied. Different homogeneous models duly validated for various pure component droplets were applied to predict the vaporization time of the feed droplets typically expected in FCC feed vaporization zone. A new physical model for heterogeneous vaporization considering droplet-particle collision mechanics was also developed in the present study which compared well with the other existing heterogeneous modelling approaches. Comparison of the two vaporization modes indicates that under typical operating conditions of FCC riser, vaporization time of feed droplets predicted by heterogeneous mode is always lower than the homogeneous mode at least by an order of magnitude due to significant increase in heat transfer coefficient which accounts for droplet-particle contact. It is expected that actual vaporization time of feed droplets in an industrial FCC riser should lie in the range predicted by these two vaporization mechanisms which actually set the two limiting modes of vaporization. Obtained results predicted by the models could be used to aid design of the FCC feed vaporization zone.